Urban villages in China: guidelines for an alternative to current demolition strategies. (1st January 2014) - Spreeuwers, Brechtje
In the past few years, international journals have published numerous theoretical analyses on China's urban villages. Architectural magazines featured practical redesigns for specific urban village sites. While the two elements could mutually reinforce each other, no research was published that combined general analysis with practical design in a systematic way. This study aims at bridging this gap and uses research and design as two interrelated components of one study to find an alternative to current demolition strategies. A literature overview and analysis of two urban villages in Shenzhen and Guangzhou formed the basis for a set of guidelines. These guidelines were tested during the design process of an urban village in Chongqing and afterwards adjusted, when needed. In this way, the resulting alternative scenario that is rooted in both theory and design provided a practical tool that aims for gradual and adaptable development while maintaining current qualities of urban villages.